Design of a servo mechanism for controlling missile fins in pitch and yaw planes - Jovičić Nebojša; Stefanović Aleksandar; Stojanović Marijana; Pavić Miloš (Scientific Technical Review)
This paper explores the design and implementation of a servo mechanism utilizing DC electromotors for control of missile fin position. This research is focused on the analysis and optimization of DC electromotors to enhance the performance of servo systems in terms of speed, torque, accuracy and efficiency. Combination of theoretical approaches and experimental test were performed to validate the proposed mechanical construction of a servo mechanism.